2007
DOI: 10.1242/dev.02837
|View full text |Cite
|
Sign up to set email alerts
|

Multiple functions of Snail family genes during palate development in mice

Abstract: Palate development requires precise regulation of gene expression changes,morphogenetic movements and alterations in cell physiology. Defects in any of these processes can result in cleft palate, a common human birth defect. The Snail gene family encodes transcriptional repressors that play essential roles in the growth and patterning of vertebrate embryos. Here we report the functions of Snail (Snai1) and Slug (Snai2) genes during palate development in mice. Snai2-/- mice exhibit cleft palate, which is comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
115
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(128 citation statements)
references
References 60 publications
(89 reference statements)
9
115
1
1
Order By: Relevance
“…4). Members of the Snail family of transcription factors are crucial regulators of palatal fusion, as Snai1 +/-; Snai2 +/-compound mutants display failure of fusion concomitant with a reduction in MES apoptosis (Murray et al, 2007). Tgfb3 expression was not affected in these mutants, however, indicating that these transcription factors regulate palatal fusion downstream of, or in parallel to, the Tgf3 pathway.…”
Section: Reviewmentioning
confidence: 98%
“…4). Members of the Snail family of transcription factors are crucial regulators of palatal fusion, as Snai1 +/-; Snai2 +/-compound mutants display failure of fusion concomitant with a reduction in MES apoptosis (Murray et al, 2007). Tgfb3 expression was not affected in these mutants, however, indicating that these transcription factors regulate palatal fusion downstream of, or in parallel to, the Tgf3 pathway.…”
Section: Reviewmentioning
confidence: 98%
“…Antisense oligonucleotides against Slug (now called Snail2) prevented neural crest and mesoderm delamination (Nieto et al, 1994) and subsequently, it was confirmed that Snail genes are crucial for the induction of EMT in different species and tissues (reviewed in Hemavathy et al, 2000;Nieto, 2002;Ip and Gridley, 2002;De Craene et al, 2005;Barrallo-Gimeno and Nieto, 2005). As such, in addition to the neural crest and the mesoderm, Snail genes participate in the EMT necessary for the formation of the heart cushions (Romano and Runyan, 2000;Carmona et al, 2000;Timmerman et al, 2004), the parietal endoderm (Velmaat et al, 2000) and the closure of the palate (Martinez-Alvarez et al, 2004;Murray et al, 2007), as well as events in other tissues and organs. Moreover, the Snail genes have been the subject of numerous evolutionary studies due to peculiarities such as the evolutionary interchange of the expression patterns of the different Snail genes in different species, and their association with the origin of the neural crest (Sefton et al, 1998;Locascio et al, 2002;Manzanares and Nieto, 2003).…”
mentioning
confidence: 91%
“…3,4 Snail homolog 2 (SNAI2), also known as Slug, has been shown to function in a manner similar to that of Snail however Slug displays a distinct tissue distribution. 5,6 During EMT, normally immobile epithelial cells in a tissue detach from neighboring cells and acquire the ability to remodel the extracellular environment and become migratory. This process is required for efficient re-epithelialization of the epidermis in response to wounding and for the migration of neural crest cells during development.…”
Section: Introductionmentioning
confidence: 99%